Structure and luminescence of SrY2O4 : Eu - Park, SJ; Park, CH; Yu, BY; Bae, HS; Kim, CH; Pyun, CH (ELECTROCHEMICAL SOC INC, 1999)
Powder samples of SrY2(1-x)O4:Eu-2x were prepared at 1000 degrees C by the combustion method. The emission spectrum of SrY2O4:Eu3+ showed two kinds of Eu3+ emissions, which could be assigned to Eu3+ ions in the Sr site and the Y site. Reducing SrY2O4:Eu brought a broad band emission around 470 nm, which could be attributed to crystal defects introduced by the reduction. The energy transfer from defects to Eu3+ ions was observed to be more effective to the Sr site than to the Y site. (C) 1999 The Electrochemical Society. S0013-4651(99)01-037-X. All rights reserved.